2005
DOI: 10.1007/s00203-005-0020-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutations affecting transcription pausing in the Bacillus subtilis pyr operon

Abstract: Pausing during transcription of the Bacillus subtilis pyr operon has been proposed to play a role in its regulation by attenuation. Substitution mutations in the B. subtilis pyr DNA specifying the 3'-terminal nucleotides of previously identified transcription pause sites substantially reduced pausing at these sites in vitro. This result confirms the general utility of this mutagenic strategy for studying transcriptional pausing. Pyrimidine-mediated repression in vivo of pyr-lacZ fusions containing some of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The E. coli and Serratia marcescens trp leader pause RNAs that were identified in vivo were identical to those found in vitro (Landick et al, 1987); however, mutations that influence pausing in vitro and gene expression in vivo have not been reported. Mutations leading to in vitro RNAP pausing defects did not appear to influence gene expression of the B. subtilis glyQS (Grundy and Henkin, 2004) or pyr (Zhang et al, 2005) operons in vivo; however, in both cases, new RNAP pause sites arose. In the case of the pyr operon, it is possible that the mutations in the nascent transcript that altered pausing in vitro led to changes in the antiterminator structure, potentially overshadowing the effect of the pause defect in vivo (Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The E. coli and Serratia marcescens trp leader pause RNAs that were identified in vivo were identical to those found in vitro (Landick et al, 1987); however, mutations that influence pausing in vitro and gene expression in vivo have not been reported. Mutations leading to in vitro RNAP pausing defects did not appear to influence gene expression of the B. subtilis glyQS (Grundy and Henkin, 2004) or pyr (Zhang et al, 2005) operons in vivo; however, in both cases, new RNAP pause sites arose. In the case of the pyr operon, it is possible that the mutations in the nascent transcript that altered pausing in vitro led to changes in the antiterminator structure, potentially overshadowing the effect of the pause defect in vivo (Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…Mutations leading to in vitro RNAP pausing defects did not appear to influence gene expression of the B. subtilis glyQS (Grundy and Henkin, 2004) or pyr (Zhang et al, 2005) operons in vivo; however, in both cases, new RNAP pause sites arose. In the case of the pyr operon, it is possible that the mutations in the nascent transcript that altered pausing in vitro led to changes in the antiterminator structure, potentially overshadowing the effect of the pause defect in vivo (Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…These findings demonstrated that transcription pausing could play an important role in the regulation of the pyr operon, but they did not demonstrate that it actually does so in vivo. In a subsequent study, Zhang et al attempted to evaluate the function of transcription pausing in the pyr operon in vivo by constructing and analyzing mutations that greatly reduce pausing (177). The mutations changed selected pyrimidine nucleotides to purine nucleotides near pause sites, which was shown to substantially reduce transcription pausing at the mutant site in vitro.…”
Section: Occurrence and Significance Of Transcriptionmentioning
confidence: 99%